The Standard ISO 15489-1 in German and Spanish: an Interlinguistic Comparison - Fernández Martín, Patricia (Revista General de Información y Documentación, 2016)
The aim of this paper is to deepen in the terminology of Records Management established by ISO standards, through a concrete example such as an interlinguistic comparison between UNE ISO 15489-1 and DIN ISO 15489-1, that is, between the Spanish and German versions of the ISO 15489-1. For that, the text is divided into two major and complementary parts, which are similar to both analytical perspectives adopted: the semantic one and the pragmatic one. The first one compares the words per se, taking into account the significant or word form as well as the significance or meaning. In the second part, examples of use from both languages are discussed, concerning the three terms considered essential in the text (Record, Records Management System and Records Management). The main conclusion lies in understanding how important the language is as a discrete tool of work for all information scientists, specially concerning to the standards, where the translators must show their best linguistic strategies to go unnoticed.